HUBUNGAN USIA IBU HAMIL DAN POLA MAKAN DENGAN KEJADIAN PREEKLAMSIA DI KLINIK RAWAT INAP NU MADINAH PUJON KABUPATEN MALANG: The Relationship Between Pregnant Women's Age And Eating Patterns With The Incidence Of Preeclampsia At NU Madinah Pujon Treat Clinics, Malang Regency - Fitria Aisyah (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Preeclampsia is a pregnancy conflict syndrome in the form of reduced organ perfusion due to vasospasm and endothelial activity. This disease generally occurs in the 3rd trimester of pregnancy, but can occur earlier. To diagnose preeclampsia, the increase in systolic pressure must be 30 mmHg or a systolic pressure above or equal to 140 mmHg or more. Or an increase in diastolic blood pressure increased by 15 mmHg or more, or diastolic pressure above or equal to 90 or more and the presence of proteinuria. The aim of this study was to see the relationship between the age of pregnant women and diet with the incidence of preeclampsia at NU Madinah Pujon Treat Clinics, Malang Regency. The sampling method used total sampling technique, namely the determination of the technique with all the population in this sample sampled. The data obtained were then analyzed using a descriptive statistical approach. By using multiple linear regression models. The t value of the variable age of pregnant women (X1) is 2,547> t table 2,048, meaning that there is a significant relationship between the age of pregnant women (X1) and the incidence of preeclampsia (Y). The t value of the dietary variable (X2) is 5,220> t table 2,048, which means that there is a significant relationship between diet (X2) and the incidence of preeclampsia (Y). The calculated F value of 16,621> from the F value of 0.05 (3.35) means that there is a significant simultaneous or simultaneous relationship between the variables of pregnant age (X1), and diet (X2), with the incidence of preeclampsia (Y). The regression value coefficient (Rsquare) of 0.552 means that the independent relationship variable with the incidence of preeclampsia is ((0.552 x 100) x 100%) 55.2%, while the other 44.8% is obtained by other factors not examined. Judging from the relationship between the two independent variables (X) on the dependent variable (Y) it can be ignored that the dietary variable X2 is more dominant in the incidence of preeclampsia (Y) as evidenced by the value of t count 5.220> t table 2.048.